2013
DOI: 10.1039/c2cp42863f
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of substrate catalyst complexes in mixtures with ultrafast two-dimensional infrared spectroscopy

Abstract: The understanding of reaction mechanisms requires structure elucidation of short-lived intermediates, even in the presence of other, similar structures. Here we show that polarization dependent two-dimensional infrared spectroscopy is a powerful method to determine the structure of molecules that participate in fast equilibria, in a regime where standard techniques such as nuclear magnetic resonance spectroscopy are beyond their limits. Using catalyst-substrate complexes in a Lewis acid catalyzed enantioselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(51 reference statements)
0
7
0
2
Order By: Relevance
“…An interesting recent application is the structural analysis of molecular conformers in organic chemical reactions. 34, 35 Knowledge of the structures adopted by small molecules is valuable for rationalizing and predicting chemical reactions, particularly those involving stereochemical control. For example, 2D IR spectroscopy has been applied to analyze the potential conformations adopted in the stereoselective Diels-Alder reaction of cyclopentadiene and N -crotonyloxazolidinone with Lewis acid catalyst SnCl 4 .…”
Section: Applications Of 2d Ir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting recent application is the structural analysis of molecular conformers in organic chemical reactions. 34, 35 Knowledge of the structures adopted by small molecules is valuable for rationalizing and predicting chemical reactions, particularly those involving stereochemical control. For example, 2D IR spectroscopy has been applied to analyze the potential conformations adopted in the stereoselective Diels-Alder reaction of cyclopentadiene and N -crotonyloxazolidinone with Lewis acid catalyst SnCl 4 .…”
Section: Applications Of 2d Ir Spectroscopymentioning
confidence: 99%
“…For example, 2D IR spectroscopy has been applied to analyze the potential conformations adopted in the stereoselective Diels-Alder reaction of cyclopentadiene and N -crotonyloxazolidinone with Lewis acid catalyst SnCl 4 . 35 2D spectra of equimolar solutions of the dieneophile substrate and SnCl 4 are shown in Fig. 2.…”
Section: Applications Of 2d Ir Spectroscopymentioning
confidence: 99%
“…Kreuzsignale kçnnen daher verwendet werden, um Banden in Spektren von Gemischen zuzuordnen und zu gruppieren. [22,31] Die Polarisationsabhängigkeit der Kreuzsignale lässt Rückschlüsse auf den Winkel zwischen den Übergangsdipolmomenten der wechselwirkenden Schwingungen zu, was zur Strukturbestimmung genutzt werden kann. [32,33] Auch die anharmonische Kopplung,w elche aus den beobachteten anharmonischen Verschiebungen bestimmt wird, kann verwendet werden, um die molekulare Struktur abzuleiten.…”
Section: Methodsunclassified
“…Die Beispiele dieses Abschnitts zeigen, dass die Analyse von transienten Strukturen mittels T2D-IR bisher nur auf sehr grundlegendem Niveau betrieben wurde.H ingegen konnte man mit 2D-IR-Spektroskopie in Gleichgewichtssystemen bereits detaillierte Strukturanalysen durchführen. [31][32][33][34]83] T2D-IR-Spektroskopie kann solch detaillierte Information auch für transiente Spezies liefern, bei denen die hohe Zeitauflçsung von Femtosekundenspektroskopie ihren vollen Nutzen entfalten kann.…”
Section: Ausblickunclassified
“…The results could prove instrumental in developing the next-generation antiviral treatments. spectrum, thereby offering unambiguous peak assignments and resolving structural isomers in a mixture (20). Our recent experiments on pyridone derivatives demonstrated that 2D IR can distinguish their lactam and lactim tautomers (21) and measure their tautomerization kinetics (16).…”
Section: Significancementioning
confidence: 99%